1988
DOI: 10.1007/978-1-4612-3936-9_7
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Our Galaxy Derived from Observations of Neutral Hydrogen

Abstract: Although insight into the structure of our Galaxy can be sought in various ways, study of the radio emission from the neutral hydrogen component is particularly suitable. Neutral atomic hydrogen, HI, is the main observed constituent of the interstellar medium; its physical properties are closely related to the properties of other Galactic constituents, both stellar and interstellar. The interstellar medium is transparent enough to hydrogen emission at the 21-cm radio wavelength that investigation of the entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(36 citation statements)
references
References 95 publications
1
34
0
1
Order By: Relevance
“…Figure 10 compares the amplitude of the warp from different authors with our result for three age class. A good agreement is obtained with Burton (1988), López-Corredoira et al (2002) and Yusifov (2004) for stars with mean age equal to 2.5 Gyr in the distance range, 10.5 < R < 13.5 kpc. However, the warp slopes were determined using tracers in different Galactocentric distance ranges.…”
Section: Warp Parameters and Originsupporting
confidence: 83%
See 3 more Smart Citations
“…Figure 10 compares the amplitude of the warp from different authors with our result for three age class. A good agreement is obtained with Burton (1988), López-Corredoira et al (2002) and Yusifov (2004) for stars with mean age equal to 2.5 Gyr in the distance range, 10.5 < R < 13.5 kpc. However, the warp slopes were determined using tracers in different Galactocentric distance ranges.…”
Section: Warp Parameters and Originsupporting
confidence: 83%
“…The asymmetry of the warp was long identified in HI gas (Burton 1988;Levine et al 2006;Kalberla & Dedes 2008) and even in stars (López-Corredoira et al 2002;Reylé et al 2009). But this is the first time that it is shown that the shape varies with the age of the tracers considered.…”
Section: Dependence Of the Warp Flare And Scale Length With Agementioning
confidence: 98%
See 2 more Smart Citations
“…Table 4 shows the LSR radial velocities of these stars (Col. 4) and the minimal distance of these stars from the Sun, obtained with the galactic rotation model of the Galaxy (Fich et al 1989) (Col. 5). The weight of the individual distance determinations stems from the assumption of an uncertainty of ±10 km s −1 caused by noncircular motion (Burton 1988), from which we can infer that the value of the distance obtained in this way has an error of 1 kpc, approximately. This makes it possible for all IRAS sources studied by Walsh et al (1997) to share their location in the galaxy with the association.…”
Section: Agementioning
confidence: 99%